Forest Resources Leader Guide: Florida 4-H Project Book - Martha C. Monroe (EDIS)
Welcome to the Leader’s Guide for the project books in the Forest Resources Series. These books were written to encourage youth–as individuals, in clubs, and in classrooms–to learn about and explore the world of forests in Florida. This manual will provide the Project Helper, Club Leader, or Teacher with interesting background information, tips for successful experiments, and ideas for extensions if youth are motivated to go beyond these books.